2017
DOI: 10.1155/2017/7167292
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of 18F-FDG PET/MRE Metrics with Inflammatory Biomarkers in Patients with Crohn’s Disease: A Pilot Study

Abstract: Background To investigate the association between 18F-FDG (Fluorodeoxyglucose) PET (positron emission tomography)/MRE (magnetic resonance enterography) metrics with the inflammatory biomarkers fecal calprotectin and C-reactive protein (CRP) in patients with Crohn's disease (CD). Methods This prospective pilot study was institutional review board (IRB) approved with informed consent obtained. Consecutive CD patients were referred to 18F-FDG PET/MRE. Patients in whom colonoscopy was performed and CRP and fecal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Semi-quantitative analysis : SUV max is the more validated semi-quantitative parameter for the evaluation of glucose uptake in IBD. To date, no defined cut-off has been identified to differentiate positive and negative findings [ 228 , 234 ]. However, a comparison between SUV max of the bowel segments involved and liver is encouraged.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semi-quantitative analysis : SUV max is the more validated semi-quantitative parameter for the evaluation of glucose uptake in IBD. To date, no defined cut-off has been identified to differentiate positive and negative findings [ 228 , 234 ]. However, a comparison between SUV max of the bowel segments involved and liver is encouraged.…”
Section: Resultsmentioning
confidence: 99%
“…[ 18 F]FDG PET/CT could be co-registered to MRI, rather than CT, significantly improving diagnostic morphological information about bowel wall and decreasing the radiation dose [ 228 , 234 , 235 ]. In different clinical protocols, [ 18 F]FDG-WBC PET/CT demonstrated a higher specificity than [ 18 F]FDG PET/CT, showing a lower radiopharmaceutical uptake in healthy GI and urinary tract, but it needs further studies [ 222 , 225 ].…”
Section: Resultsmentioning
confidence: 99%
“…Over the past few years attention has turned to the possible role of FDG-PET/MRI scanners, which has the potential to not only combine the good image qualities of MRI, a well-known tool in IBD, with the functional component of FDG-PET, but also to reduce the radioactive burden. In a prospective pilot study enrolling 21 patients with known CD, Domachevsky et al found that adding apparent diffusion coefficient (ADC) and metabolic inflammatory volume (MIV) to MaRIA score resulted in an AUC of 0.92 (compared to MaRIA alone with an AUC of 0.63) resulting in 83% sensitivity and 100% specificity 41 .…”
Section: Novel Approaches -Quantification and Pet/mrimentioning
confidence: 99%
“…With the often younger population of IBD-patients in mind, this disease complex may be one of the most interesting indications for hybrid PET/MRI, and several reports are emerging within several of the aforementioned subdomains. In 21 consecutive CD patients, Domachevsky et al demonstrated the correlation between imaging and biomarkers with an increase in AUC from 0.63 to 0.92 with sensitivity and specificity of 83% and 100%, respectively, and concluded that FDG-PET/MRI significantly increased accuracy in discriminating active from non-active inflammation(64). This correlation may even be present in pre-symptomatic subclinical patients; Shih et al found correlating increased ADC and SUVmax in bowel segments with corresponding endoscopic signs of active inflammation even in patients in perceived clinical and biochemical remission(65).…”
mentioning
confidence: 99%